Carbon‐coated current collectors in lithium‐ion batteries and supercapacitors: Materials, manufacture and applications - Hongqing Hao; Rui Tan; Chunchun Ye; Chee Tong John Low (Carbon Energy)
Abstract The current collector is a crucial component in lithium‐ion batteries and supercapacitor setups, responsible for gathering electrons from electrode materials and directing them into the external circuit. However, as battery systems evolve and the demand for higher energy density increases, the limitations of traditional current collectors, such as high contact resistance and low corrosion resistance, have become increasingly evident. This review investigates the functions and challenges associated with current collectors in modern battery and supercapacitor systems, with a particular focus on using carbon coating methods to enhance their performance. Surface coating, known for its simplicity and wide applicability, emerges as a promising solution to address these challenges. The review provides a comprehensive overview of carbon‐coated current collectors across various types of metal and nonmetal substrates in lithium‐ion batteries and supercapacitors, including a comparative analysis of coating materials and techniques. It also discusses methods for manufacturing carbon‐coated current collectors and their practical implications for the industry. Furthermore, the review explores prospects and opportunities, highlighting the development of next‐generation high‐performance coatings and emphasizing the importance of advanced current collectors in optimizing energy device performance.